Mutual inductance estimation of multiple input wireless power transfer for charging stationary vehicles in parking spaces - Le Kang; Haodong Yang; Song Hu (AIP Advances, 2020)
The electric vehicle (EV) is the future of the modern automotive industry. However, the transmission performance of traditional wireless charging is highly influenced by the misalignment error between the transmitter and the receiver. This paper proposes a maximum power control method for the multiple transmitter coil wireless charging system, which can be used to charge stationary EVs freely and effectively in a wider range. An accurate and reliable mutual inductance estimation method is introduced to estimate M relying on the electric information on the transmitter side only without using empirical formulas and additional communication devices between both sides. Then, the paper proposes a control method, which can maximize the output power in a quite wider range. Experiments and simulations prove that the proposed method has a good performance on charging a receiver coil effectively in a wider range; therefore, it is suitable for charging stationary EVs in the parking space.